Prevalence of malnutrition in children under five years old in Beira city, Mozambique, 2019 - Matias Joaquim Culpa; Denise Oliveira e Silva; Nathália Paula de Souza; Alessandro Henrique da Silva Santos; André Luiz Sá de Oliveira; Eduarda Ângela Pessoa Cesse (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Objectives: to describe the prevalence of malnutrition (underweight, low height, and overweight) in children aged six to 59 months and its spatial distribution in the city of Beira, Mozambique. Methods: an exploratory cross-sectional study was conducted between October and November 2019, involving 407 children aged six to 59 months. The sample size calculation was based on the prevalence of height-for-age deficit. Anthropometric data were analyzed using Anthro version and the prevalence of malnutrition was presented through thematic maps generated in Quantum Geographic Information System (QGIS). Results: the main findings revealed a prevalence of 27.0% for low height/age, 7.9% for underweight/height, and 4.7% for overweight. Conclusions: the spatial distribution highlighted that both urban and peri-urban areas of the city showed similar prevalence rates for the three forms of malnutrition. The prevalence of malnutrition in Beira is high, with deficit height/age being the most significant expression, while overweight is diffusely distributed.